2018
DOI: 10.1177/0049475518786835
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of single dose albendazole and praziquantel drugs among helminth-infected school children at Rural Bahir Dar, northwest Ethiopia

Abstract: The resistance of anthelminthic drugs makes helminth control difficult. The aim of our study was to assess the efficacy of single dose albendazole and praziquantel drugs among helminth-infected children. A cross-sectional study was conducted from April to June, 2017. Stool examination was done by the Formol-Ether concentration technique. Students infected with geohelminths and s chistosoma mansoni were treated with a single dose of albendazole and praziquantel, respectively. Post-treatment stool examination wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
5
6
2
Order By: Relevance
“…The results of this study show that PZQ efficacy was satisfactory even after the first dose of treatment, as indicated by an ERR of more than 90%. This result is in line with a satisfactory PZQ efficacy reported in several countries in Africa for treatment of S. haematobium infection [3032] as well as for S. mansoni [29, 30, 33], although in these studies the regimen was 40 mg/kg. However, in contrast, other studies have reported a doubtful efficacy of PZQ in school children [3].…”
Section: Discussionsupporting
confidence: 86%
“…The results of this study show that PZQ efficacy was satisfactory even after the first dose of treatment, as indicated by an ERR of more than 90%. This result is in line with a satisfactory PZQ efficacy reported in several countries in Africa for treatment of S. haematobium infection [3032] as well as for S. mansoni [29, 30, 33], although in these studies the regimen was 40 mg/kg. However, in contrast, other studies have reported a doubtful efficacy of PZQ in school children [3].…”
Section: Discussionsupporting
confidence: 86%
“…22 In the present study, hookworm was the most frequent STH infections (29.4%). This result was consistent with the previous findings performed in rural Bahir Dar, 13 and in rural highlands of northwest Ethiopia 14 and India, 23 but higher than the previous result obtained in Ambo town in western Ethiopia. 16 The difference might be due to the difference in diagnostic method, sample size, and geographical location.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the overall prevalence of STH infections was 34.5%. This result was lower than the previous result obtained (43.0%) in rural Bahir Dar, 13 (69.2%) in rural Amhara region, 14 and (49.0%) in Jimma town. 15 This result was also higher than the previous report obtained (12.6%) in Ambo, west Ethiopia.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In the present study, the prevalence of intestinal helminths at 95% CI was 51.2% (46.4-55.9%). This result is lower than the previous studies conducted in rural Bahir Dar (58%) [16] and Zarima town 82.4% [17]. This result is also comparable with the previous (54.9%) prevalence report in Durbetie town [18] but higher than a report in Libo-Kemkem (27.9%) [19] and (16.7%) in Gondar town [20].…”
Section: Discussionsupporting
confidence: 80%